INVERSE NODAL PROBLEM FOR p-LAPLACIAN DIFFUSION EQUATION WITH POLYNOMIALLY DEPENDENT SPECTRAL PARAMETER - Gulsen, Tuba; Yilmaz, Emrah (Ankara Univ, Fac Sci, 2016)
In this study, solution of inverse nodal problem for one-dimensional p-Laplacian diffusion equation is extended to the case that boundary condition depends on polynomial eigenparameter. To find the spectral datas as eigenvalues and nodal parameters of this problem, we used a modified Prufer substitution. Then, reconstruction formula of the potential function is also given by using nodal lenghts. Furthermore, this method is similar to used in [1], our results are more general.
Keywords: Inverse Nodal Problem; Prufer Substitution; Diffusion equation